Juli Francesc Guibernau: un escriptor popular de l’època de la restauració - Cassany, Enric (Caplletra. Revista Internacional de Filologia, 2005)
The present article speaks about Juli Francesc Guibernau, a festive author who obtained a great popularity under the pseudonym of C. Gumà during the decades of 1880 and 1890. The articles published in «La Campana de Gràcia» and «L’Esquella de la Torratxa», the comedy sketches and, particularly, the festive poetry notebooks given to the public by «Llibreria Espanyola», which belonged to López publishers, conform the image of a popular writer at the close of the nineteenth century. They also attest the transformations of the popular culture and the social and moral changes of the society in Barcelona and Catalonia at the time of the Restoration. The article locates Guibernau in the popular trend that goes from Pitarra to Rusiñol, and uses it as a pretext to comment on the problematic relation between popular and highbrow literature in the industrial society, together with the denial or the demands of the popular inheritance made by later generations in the eighteenth century.